School-based management and special education program and services in selected school divisions - Yap, Ingrid R. (2008)
This study aimed to survey the effects of School-Based Management on special education programs and services specifically in Inclusive Education. The research used a three level method to generate data for the study. A focus group discussion was conducted with the principals, then an item pool was developed and used to produce a final questionnaire to be administered to the selected respondents. Interviews were also conducted with stakeholders in the SPED IE project. Findings showed that TEEP-SBM that practice Inclusive Education was advantageous to students with special needs. Strong linkages with stakeholders, parents, locals government units, and the community were built during the project. To sustain the gains achieved by the TEEP-SBM project, the SPED teachers recommend continuous training on inclusive education for both regular and special education teachers.
Computer printout.
Thesis (Ph.D. Special Education)--University of the Philippines, Diliman.
Keywords: Special education -- Philippines -- Administration; Inclusive education -- Philippines; Children with disabilities -- Education -- Philippines; School-based management -- Philippines